Bupivacaine Induces Short-Term Alterations and Impairment in Rat Tendons. (June 2013) - Lehner, Christine; Gehwolf, Renate; Hirzinger, Corinna; Stephan, Daniel; Augat, Peter; Tauber, Mark; Resch, Herbert; Bauer, Hans-Christian; Bauer, Hannelore; Tempfer, Herbert
Background: Toxicity of the local anesthetic bupivacaine (BV) has been a matter of debate across medical fields. Numerous in vitro studies demonstrate considerable toxicity of BV on various cell types. Purpose: This study addresses the question of how tendon tissue responds to BV in vivo and in vitro. Study Design: Controlled laboratory study. Methods: In vitro studies on cultured rat Achilles tendon–derived cells were performed with cell viability assays and cleaved caspase 3 immunocytochemistry. Quantitative reverse transcription–polymerase chain reaction, Western blotting, gelatin zymography, and a biomechanical testing routine were applied on rat Achilles tendons at 1 and 4 weeks after a single unilateral peritendinous injection of 0.5% BV. The BV-mediated cell death in tendons was estimated with terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining and immunohistochemical detection of cleaved caspase 3. Results: Treatment of rat tendon–derived cells with 0.5% bupivacaine for 10 minutes had detrimental effects on cell viability, which can be reduced by N-acetyl-L-cysteine or reduction of extracellular calcium. In vivo, single peritendinous injections of BV caused apoptosis in endotenon cells and an increase of pro–matrix metalloproteinase-9 after 6 hours. The collagen ratio shifted toward collagen type III after 6 hours and 2 days; scleraxis messenger RNA (mRNA) expression was reduced by 87%. Maximum tensile load was reduced by 17.6% after 1 week. Conclusion: Bupivacaine exerts a severe, reactive oxygen species–mediated effect on tendon cell viability in vitro in a time- and dose-dependent manner, depending on extracellular calcium concentration. Culture conditions need to be taken into account when in vitro data are translated into the in vivo situation. In vivo, administration of BV elicits a marked but temporary functional damage. Clinical Relevance: Local anesthetics cause short-term alterations in rat tendons, which, if occurring in humans to a similar extent, may be relevant regarding decreased biomechanical properties and increased vulnerability to tendon overload or injury.